https://imgur.com/a/nMeLwip
Not sure what to do with this problem:
I know that the difference is the same for p_(0)-p_(1)=p_(1)-p_(2)=p_(2)-p_(3)=p_(3)-p_(4)=p_(4)-p_(5)
I know we are looking for p_(4)+p_(5)
https://imgur.com/a/nMeLwip
Not sure what to do with this problem:
I know that the difference is the same for p_(0)-p_(1)=p_(1)-p_(2)=p_(2)-p_(3)=p_(3)-p_(4)=p_(4)-p_(5)
I know we are looking for p_(4)+p_(5)
I would approach it as an arithmetic progression where a is P(0) and the common difference is d.
So the terms are a, a+d, a+2d, a+3d, a+4d, a+5d.
All of these add to 1 (total of probabilities). The first 2 add to 0.4. This will give 2 simultaneous equations. Then find sum of last 2.